2016
DOI: 10.1016/j.ejrad.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced perfusion area detector CT for non-small cell lung cancer patients: Influence of mathematical models on early prediction capabilities for treatment response and recurrence after chemoradiotherapy

Abstract: Mathematical models have significant influence on assessment for early prediction of treatment response, disease progression and overall survival using dynamic CE-perfusion ADCT for NSCLC patients treated with chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 27 publications
2
60
0
Order By: Relevance
“…and Ohno et al . also demonstrated that DCTP analysis is useful in the prediction or early assessment of the treatment effect of chemoradiotherapy for non‐small cell lung cancer (NSCLC) …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…and Ohno et al . also demonstrated that DCTP analysis is useful in the prediction or early assessment of the treatment effect of chemoradiotherapy for non‐small cell lung cancer (NSCLC) …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proposed that DCTP analysis is valuable in clinical use to estimate the hemodynamics of lung cancer . Some of these studies involved inter‐observer agreement analysis to measure advanced NSCLC or intra‐observer and inter‐observer agreement analysis to measure lung nodules .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This noninvasive and widely available methodology allows obtaining time concentration curves (TCCs) pertaining to a specific region of interest (ROI) by repeatedly acquiring the same portion of tissue during, and after, the intravenous injection of an iodinated contrast agent [2]. Through the analysis of TCCs, it is possible to achieve colorimetric maps representing values of perfusion parameters that can be used for multiple purposes such as monitoring vascular changes after the administration of antiangiogenic drugs [3], predicting tumour response [4, 5], or differentiating tumour subtypes [6]. …”
Section: Introductionmentioning
confidence: 99%